A Nonclassical IFITM5 Mutation Located in the Coding Region Causes Severe Osteogenesis Imperfecta With Prenatal Onset. (June 2014) - Hoyer‐Kuhn, Heike; Semler, Oliver; Garbes, Lutz; Zimmermann, Katharina; Becker, Jutta; Wollnik, Bernd; Schoenau, Eckhard; Netzer, Christian
ABSTRACT Osteogenesis imperfecta (OI) is a hereditary connective tissue disorder characterized by a wide range of skeletal symptoms. Most patients have dominantly inherited or de novo mutations in COL1A1 or COL1A2. Up to 5% of patients have OI type V, characterized by hyperplastic callus formation after fractures, calcification of the interosseous membrane of the forearm, and a mesh‐like lamellation pattern observed in bone histology. Recently, a heterozygous mutation in the 5′‐untranslated region (UTR) of IFITM5 (c.–14C > T) was identified as the underlying cause of OI type V, and only this specific mutation was subsequently identified in all patient cohorts with this OI subtype. We now present a case of a heterozygous mutation within the coding region of IFITM5 (c.119C > T; p.S40L). The mutation occurred de novo in the patient and resulted in severe OI with prenatal onset and extreme short stature. At the age of 19 months, the typical clinical hallmarks of OI type V were not present. Our finding has important consequences for the genetic "work‐up" of patients suspected to have OI, both in prenatal and in postnatal settings: The entire gene—not only the 5′‐UTR harboring the "classical" OI type V mutation—has to be analyzed to exclude a causal role of IFITM5. We propose that this should be part of the initial diagnostic steps for genetic laboratories performing SANGER sequencing in OI patients. © 2014 American Society for Bone and Mineral Research.